DNA damage response regulator ATR licenses PINK1-mediated mitophagy - Marx, Christian; Qing, Xiaobing; Gong, Yamin; Kirkpatrick, Joanna; Siniuk, Kanstantsin; Beznoussenko, Galina V.; Kidiyoor, Gururaj Rao; Kirtay, Murat; Buder, Katrin; Koch, Philipp; Westermann, Martin; Bruhn, Christopher; et al. (Nucleic acids research, 2025)
Defective DNA damage response (DDR) and mitochondrial dysfunction are a major etiology of tissue impairment and aging. Mitochondrial autophagy (mitophagy) is a mitochondrial quality control (MQC) mechanism to selectively eliminate dysfunctional mitochondria. ATR (ataxia-telangiectasia and Rad3-related) is a key DDR regulator playing a pivotal role in DNA replication stress response and genomic stability. Paradoxically, the human Seckel syndrome caused by ATR mutations exhibits premature aging and neuropathies, suggesting a role of ATR in nonreplicating tissues. Here, we report a previously unknown yet direct role of ATR at mitochondria. We find that ATR and PINK1 (PTEN-induced kinase 1) dock at the mitochondrial translocase TOM/TIM complex, where ATR interacts directly with and thereby stabilizes PINK1. ATR deletion silences mitophagy initiation thereby altering oxidative phosphorylation functionality resulting in reactive oxygen species overproduction that attack cytosolic macromolecules, in both cells and brain tissues, prior to nuclear DNA. This study discloses ATR as an integrated component of the PINK1-mediated MQC program to ensure mitochondrial fitness. Together with its DDR function, ATR safeguards mitochondrial and genomic integrity under physiological and genotoxic conditions.
Gesehen am 17.02.2026